2010
DOI: 10.4314/eamj.v86i8.54159
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic paediatric diarrhoeal illness in urban and rural sites in Nyanza province, Kenya

Abstract: Objective: Investigate differences in the infectious aetiology, health seeking behaviour, and provider practices with regard to diarrhoeal illness among children presenting to urban versus rural clinics in Western Kenya. Design: Laboratory-based, passive surveillance. (24% urban, 25% rural). Campylobacter was the predominant bacterial pathogen (17% urban, 15% rural), followed by Shigella and nontyphoidal Salmonella (both 4% urban and 5% rural). In both communities, susceptibilities of these pathogens to the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
1
12
2
Order By: Relevance
“…In the current study, all isolates were susceptible or moderately susceptible to erythromycin. Unlike some surveillances (20,23,(28)(29)(30)(31)(32)(33)(34), we did not find macrolide-resistant strains.…”
Section: Discussioncontrasting
confidence: 99%
“…In the current study, all isolates were susceptible or moderately susceptible to erythromycin. Unlike some surveillances (20,23,(28)(29)(30)(31)(32)(33)(34), we did not find macrolide-resistant strains.…”
Section: Discussioncontrasting
confidence: 99%
“…However, a high rate in young adults comparable to that in children can be associated with a common source of contamination: indeed, these young adults in Burkina Faso are workers who eat in the street, outside of their house. Neither schooling, nor the level of education were risk factors to enteritis due to Campylobacter, contrary to data reported in a study in Jordan where education was a risk factor that correlated significantly with diarrhea due to Campylobacter enteritis (27) than 95% of the patients came from Ouagadougou and the others were also city-dwellers: these findings are comparable to those reported by Beatty et al, (28) reported (1, 30). The clinical manifestations and substantial mortality are more frequent in AIDS patients than HIV-negative patients (1, 24, 31).…”
Section: Bacteriological Datacontrasting
confidence: 64%
“…The rate may be lower than 10% in other developing countries, (41). However, the Campylobacter resistance to fluoroquinolones is high (11-95%) and continue to increase in developing countries, globally, particularly in Thailand (16,28,37). The data reported in Burkina Faso (Table 2) is in keeping with this trend.…”
Section: Bacteriological Datamentioning
confidence: 57%
See 2 more Smart Citations